Analysis Stylistic in The Novel Sepi by Pijar Psikologi: Analisis Stilistika dalam Novel Sepi Karya Pijar Psikologi - Annisa Amelia Zakiyah; Ahada Wahyusari; Dody Irawan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research describes stylistics as the science that delves into literary studies by applying the principles of stylistic language found in the novel